Effect of Cooking Procedure on B1, B2, and B6 Vitamins Content and Some Elements in the Main Rice Brands in the Iranian Market - Asadikaram, Gholamreza; Norouzi, Saam; Khalili, Tahereh; Abolhassani, Moslem; Torkzadeh-Mahani, Masoud; Hajizadeh, Mohammad R.; Vahabzadeh, Zakaria (Current Nutrition & Food Science, 2024)
Aims: The aim of the present study was to assess and compare the effect of different methods of cooking on B-group vitamins (B1, B2, and B6), As, Cd, Ni, Pb, and some essential elements (Cu, Co, and Mn) in the main local varieties of Iranian rice.Background: Different cooking procedures have been shown to have contradictory benefits in terms of nutritional value by affecting the bioavailability of vitamins and microminerals.Objective: The aim of the present study was to assess and compare the effect of different methods of cooking on B-group vitamins (B1, B2 and B6), As, Cd, Ni, Pb, and some essential elements (Cu, Co, and Mn) in the main local varieties of Iranian rice.Methods: The effectiveness of different cooking procedures, including direct cooking (Dampokht) and cooking by washing the rice with water and draining off the water (Abkesh), on B1, B2, and B6 vitamins contents and Cd, As, Pb, Ni, Cu, Co, Mn elements in the different local varieties of Iranian rice was evaluated. For the Dampokht method, the non-rinsed cooked samples were directly used for evaluation, but for the Abkesh method, the cooked rice samples were first rinsed and then evaluated.Results: Generally, our results showed decreased levels of vitamins and trace elements in cooking with the Abkesh method in comparison to that of Dampokht. Interestingly, the amount of B1 vitamin increased after the Dampokht method.Conclusion: The results indicate that the rice cooking procedure is very important in the maintenance of B vitamins and trace elements in the foodstuff, and the Abkesh method leads to the loss of a great deal of water-soluble vitamins and essential elements. However, it is good for decreasing poisonous heavy metals and should be recommended for populations that consume rice as the main staple food and who live in the areas with a high level of toxic heavy metals in drinking water.
Keywords: Rice cooking procedure